IMPACT OF BEHAVIORAL ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB): THE MODERATION ROLE OF JOB SATISFACTION - Heri Soesanto; Nasikh Nasikh (Aktiva : Jurnal Akuntansi dan Investasi, 2022)
In the current situation of inter-company competition, human resource development is key to the development and achievement of company goals. This study aims to examine the effect of behavior on Organizational Citizenship Behavior (OCB) and examine the role of job satisfaction as a moderating variable in the influence of behavior on OCB in one of food and beverage companies in Indonesia. The purpose of this study was to determine the effect of organizational commitment, leadership style, and organizational culture on the OCB and to determine the role of job satisfaction in the relationship between organizational commitment, leadership style, and organizational culture with OCB. The sample consists of 4,062 employees at the company. Data were analyzed using PLS-SEM with the SmartPLS application.The results showed that organizational commitment has an effect on OCB, leadership style has no effect on OCB, organizational culture has an effect on OCB. Furthermore, job satisfaction moderated the relationship between organizational commitment and OCB, but job satisfaction does not moderate the relationship between leadership style and OCB, as well as the relationship between organizational culture and OCB.